Aza-[4 + 2]-cycloaddition of benzocyclobutenones into isoquinolinone derivatives enabled by photoinduced regio-specific C–C bond cleavage - Liangkun Yang; Shiyang Li; Lichao Ning; Hansen Zhao; Liang Zhou; Weidi Cao; Xiaoming Feng (Nature Communications)
Abstract The activation of C−C bond of benzocyclobutenones under mild reaction conditions remains a challenge. We herein report a photoinduced catalyst-free regio-specific C1−C8 bond cleavage of benzocyclobutenones, enabling the generation of versatile ortho-quinoid ketene methides for aza-[4 + 2]-cycloaddition with imines, which offers a facile route to isoquinolinone derivatives, including seven family members of protoberberine alkaloids, gusanlung A, B, D, 8-oxotetrahydroplamatine, tetrahydrothalifendine, tetrahydropalmatine, and xylopinine. Furthermore, the catalytic enantioselective version of this strategy is also realized by merging synergistic photocatalysis and chiral Lewis acid catalysis. Mechanistic studies provide compelling evidence to rationalize the photoisomerization/cycloaddition cascade process.